JENIS-JENIS IKAN INTRODUKSI DI PERAIRAN TAWAR JAWA BARAT DAN BANTEN: CATATAN TENTANG TAKSONOMI DAN DISTRIBUSINYA [Introduced Fishes to Inland Waters in West Java and Banten: Some Notes on its Taxonomic and Distribution] - Ike Rachmatika; G Wahyudewantoro (Jurnal Iktiologi Indonesia, 2006)
During survey of the fish diversity of the streams at the Gunung Halimun National Park, Gunung Ciremai National Park, Southern Kuningan regency and Garut regency, at least ten species of introduced fishes were found. They were Cyprinus carpio (Cyprinidae), Liposarcus pardalis (Loricariidae), Clarias gariepinus (Clariidae), Poecilia reticulata, P. latipinna, Xipophorus hellerii (Poeciliidae), Cichlasoma nigrofasciatum, Aequidens pulcher, Oreochromis niloticus, O. mossambicus (Cichlidae) and Trichogaster pectoralis (Belontiidae). In general, the populations of these species have established in the waters. The impact of these introduced fishes on the native species is discussed.